Hubungan Tingkat Pendidikan Formal Ibu dengan Pengetahuan tentang Pemberian ASI Eksklusif di Puskesmas Ngoresan - Anggasari, Narulita; Siregar, Rustam; Sumardyono, . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Exclusive breastfeeding is very important for the growth and development of infants. Thus, nursing mothers need to improve their knowledge about exclusive breastfeeding. The aims of this study were to investigate the relationship between the mothers formal education and counseling with motherâs knowledge of exclusive breastfeeding in Ngoresan primary health care. Methods: The population were mothers with children age 0-6 months in Ngoresan primary health care region.Thirty samples were taken by using purposive quota sampling technique. Those mothers were asked to fill out a questionnaire about exclusive breastfeeding (pretest), then they were given counseling of exclusive breastfeeding by researchers. Finally they filled out the same questionnaires again (posttest). We analized the correlation of formal education, age, economic status and job with knowledge of exclusive breastfeeding from the pretest and posttest, all done with p value<0.05 considered significant. Results: Spearmanâs Rho test was used to analyze the relation of exclusive breastfeeding knowledge with formal education, age, economic status and job. It revealedÂ that higher motherâs formal education, more they know about exclusive breastfeeding (p=0.001). While age, economic status and job did not affect their knowledge of exclusive breastfeeding (p>0.05). Pretest and posttest analysis used Wilcoxon test (p=0.000). It suggested that educated mothers about exclusive breastfeeding can increase their knowledge of exclusive breastfeeding. Conclusion: Counseling and motherâs formal education have an important role in improving their knowledge of exclusive breastfeeding. Keywords: : knowledge, breastfeeding, counseling. Â